Community Pharmacists’ Contribution During a Public Health Crisis Such as COVID-19 - Nazaryan, Lusine Gagik; Barseghyan, Aush Barseg; Simonyan, Marta Hektor (Caucasus Journal of Health Sciences and Public Health, 2020)
Background: Community pharmacy is one of a number of health professions that has a key role to play in responding to the current pandemic. Aim and objective was to study the problems in the midst of public health crisis of the current magnitude with the roles and activities of pharmacists. Methodology: The study was carried out among 384 consumers using pharmacy in the regions of Armenia and Yerevan. Primary information was collected using a questionnaire. The results were analyzed with SPSS statistical software, version 12.0. Result: During the study it becomes clear that 37% of pharmacy consumers have different health problems diagnosed by the doctors. Most of them don’t trust the information provided by pharmacy employees. Very few of consumers are clearly satisfied with the answers of a pharmacy employee (29%). Conclusion. In the midst of the current public health crisis community pharmacist can potentially reduce GPs’ minor ailment-related workload. There is a need to develop pharmaceutical care algorithms for minor ailments, national emergency drug formularies for public health crises such as COVID-19.